ON SOME LIMNOLOGICAL ASPECTS OF THE KHARI NADI IN AGRA - SOLANKI, SUNITA; RANA, K.S.; SINGH, ARUN KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
The present communication deals with the distribution and seasonal variation of certain physico-chemical parameters of water of Khari Nadi situated in the Kheragarh of Agra district (U.P.) during the year 2002. The probable causes of variations of these parameters have also been discussed.